Neglected effect of transportation on the property of municipal biowaste and the subsequent biomethane potential. (10th June 2022) - Nie, Erqi; He, Pinjing; Zou, Jinlin; Zhang, Hua; Lü, Fan
Abstract: Long-distance transportation of municipal biowaste can influence its physio-chemical characteristics and the subsequent anaerobic digestion (AD) performance. However, the effect of whole transportation processes on the characteristics of municipal biowaste from upstream source separation/collection to downstream storage remains poorly documented. To this end, this study presented the relevant work by sampling in practical conditions. Results showed that transportation led to a high hydrolysis rate of 33.4%–35.5%, and an acidification rate of 15.8%–17.3%. Simultaneously, lactic acid was produced to a concentration of 18.1 g/L, occupying approximately 20% of dissolved organic carbon. Furthermore, the highest cumulative CH4 production was observed at the samples of source separation/collection (398 ± 52–519 ± 117 mL/gVS for FW, 276 ± 51–332 ± 41 mL/gVS for KW), and then accompanied by a decrease (299 ± 31 mL/gVS for FW and 285 ± 39 mL/gVS for KW) after downstream storage. The results indicated that the subsequent anaerobic digestion would be inclined to appear perturbation caused by the lactic acidification of the initial feed and it is imperative to avoid further conversion of lactic acid to propionic acid, which could provide vital guideline reference for the optimization of biogas production process. Moreover, the lactic acid-rich property also highlights other value-added pathways for the resource recovery of municipal biowaste. Graphical abstract: Image 1 Highlights: Practical transportation of municipal biowaste was investigated. The hydrolysis process of biowaste primarily occurred during transportation. Transportation and storage of biowaste promoted lactic acid production. Lactic acid severely accumulated and occupied approximately 20% of DOC. The CH4 production decreased along with the prolonging of transportation.